In vitro comparison of coronal microleakage of four temporary restorative materials used in endodontic treatment - Shahi Sh; Molaee Asl A. (Tehran University of Medical Sciences, 2008)
"nBackground and Aim: The use of proper temporary restorative materials between appointments is critical in successful root canal treatment. The purpose of this study was to compare the coronal microleakage of four temporary restorative materials including Zonalin, Zamherir, Coltosol and IRM. "nMaterials and Methods: In this in vitro study, standard access cavities were prepared in 120 intact extracted maxillary and mandibular human first molars. Canal preparation was carried out by the step-back technique, and obturation was performed with gutta-percha and AH26 sealer using the lateral condensation technique. Teeth were randomly divided into 4 experimental groups of 25 teeth each and two positive and negative control groups, each containing 10 teeth. In each experimental group the access cavity was restored with one of the tested materials (Zamherir, Zonalin, IRM and Coltosol). In the negative control group the access cavity was filled entirely with sticky wax and in the positive control group no restorative material was applied. Dye penetration technique was used to evaluate microleakage which was measured under a stereomicroscope. Data were analyzed with one way ANOVA and post hoc Tukey tests. P<0.05 was considered as the limit of significance. "nResults: Dye penetration was observed in all groups. Zonalin and Coltosol had the highest and the lowest dye penetration respectively, with a statistically significant difference (p<0.001). There was no significant difference in dye penetration between IRM, and either Coltosol or Zamherir (p>0.05). "nConclusion: The results of this study showed that using Coltosol as a temporary restorative material can provide a better coronal seal in endodontic treatments